Extraction of sunflower head pectin with superfine grinding pretreatment. (1st August 2020) - Tan, Jing; Hua, Xiao; Liu, Jingran; Wang, Mingming; Liu, Yaxian; Yang, Ruijin; Cao, Yanping
Graphical abstract: Highlights: Sunflower head was pretreated by superfine grinding to microparticles of ~50 μm. Pectin chains were fully exposed after cell wall breakdown by superfine grinding. High pectin yield was achieved at mild conditions associated with sodium citrate. Different pectins were obtained with or without inactivation of endo-pectinase. Pectin extracted at different conditions presented various rheological properties. Abstract: Effect of superfine grinding on pectin extraction was investigated. Sunflower heads were grinded into microparticles of ~50 μm, thus pectin chains were fully exposed due to cell wall breakdown. A good pectin yield of 14.5 ± 0.36% (w/w) was subsequently achieved at mild conditions (pH 5.0, 25 °C, 2 h) associated with 0.8% (w/v) sodium citrate (SC). However, the molecule weight of pectin was greatly reduced (Mw  = 7.87 ± 0.21 kDa) due to the action of endo-pectinases. With heating (pH 5.0, 85 °C for 20 min, 25 °C for 1.5 h) the endo-pectinases were effectively inhibited, thus Mw was increased to 338.07 ± 12.37 kDa. With superfine grinding, pectin extracted with different conditions presented various properties. Pectin extracted at pH 2.5 had higher esterification degree (DE, ~40%) and gelled at 3% (w/v) concentration. In contrast, pectin extracted under mild condition with low DE (21%) cannot gel at the same concentration. Conclusively, superfine grinding has potential application in pectin extraction.